Expanding the boundaries of freedom. The democratic opposition in Czechoslovakia from 1978 to 1989 and the inspiration from the thought of John Paul II - Brodniewicz, Joanna (Poznańskie Studia Slawistyczne, 2025)
The Czech democratic opposition from the mid-1970s until the Velvet Revolution was a unique phenomenon in Central Europe. One of its defining features was its ability to bring together diverse groups. It sought ways to broaden both external and internal freedoms. The election of Karol Wojtyła as pope on 16 October 1978 was among the events that gave Czech dissidents renewed hope for change. His actions inspired parts of the democratic opposition from various milieus to push back the boundaries of freedom.